Effect of a neck collar on upper airway size in children sedated with propofol–midazolam combination during magnetic resonance imaging. Issue 4 (12th January 2015) - Moustafa, Moustafa A.; Emara, Doaa M.; Nouh, Mohamed R.; Cote, Charles
Summary Introduction Propofol and midazolam are widely used for pediatric magnetic resonance imaging (MRI) sedation. Increasing depth of sedation may be associated with airway obstruction. A neck collar supporting the mandible and maintaining the head in slight extension may be beneficial in maintaining airway patency. Aim of the study Primary aim: To assess upper airway size with and without a neck collar during pediatric MRI sedation with propofol–midazolam. Secondary aim: To evaluate complications encountered during the procedure. Materials and Methods Sixty patients aged 2–4 years scheduled for MRI of the brain were selected. They were sedated with intramuscular midazolam 0.1 mg·kg−1 30 min before the procedure. Patients were sedated with i.v. propofol 1 mg·kg−1 and continued with 50–100 μg·kg−1·min−1. T1 3D fast‐field echo axial sequence from the nasopharyngeal roof to subglottic region was taken with and without application of a neck collar. Airway dimensions were measured and analyzed at the base of the tongue, soft palate, and at the epiglottis. Results At the base of the tongue and soft palate, the cross‐sectional area (CSA) and the anteroposterior diameter of the airway were respectively statistically significantly higher when the neck collar was applied. The CSA at the epiglottis was significantly less with application of the neck collar. Complications were not significantly different between the two sequences. Conclusion Application of a soft neck collar in children aged 2–4 years may enhance the retropalatal and retroglossal airway dimensions during pediatric sedation in the supine position.